2008
DOI: 10.1159/000149718
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone Resistance and Correlation to Other Antimicrobial Resistances in Faecal Isolates of <i>Escherichia coli</i> in Hong Kong

Abstract: In an attempt to assess the level of quinolone resistance and its association with other antimicrobial resistance in faecal Escherichia coli isolated from routine outpatient specimens in Hong Kong, ciprofloxacin-supplemented MacConkey agar was used to screen for resistant isolates. Antimicrobial susceptibility testing of the isolates was done by VITEK 2 and previous amplification-based methods were employed to characterize the genetic determinants behind some of the resistance phenotypes. One hundred and seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It was also noted that the isolates with intermediate resistance were found mostly in K. pneumoniae, which was explained by the high prevalence of bla DHA-1 containing qnrB4 in K. pneumoniae in this collection. Another report from Korea and Hong Kong also showed that the presence of PMQR genes was significantly associated with ciprofloxacin resistance in K. pneumoniae , but not in E. coli isolates [18,25] . Although it is still possible that other PMQR genes not yet identified are prevalent in E. coli , the above findings suggest that K. pneumoniae is more likely to develop fluoroquinolone resistance by obtaining PMQR genes than E. coli .…”
Section: Discussionmentioning
confidence: 94%
“…It was also noted that the isolates with intermediate resistance were found mostly in K. pneumoniae, which was explained by the high prevalence of bla DHA-1 containing qnrB4 in K. pneumoniae in this collection. Another report from Korea and Hong Kong also showed that the presence of PMQR genes was significantly associated with ciprofloxacin resistance in K. pneumoniae , but not in E. coli isolates [18,25] . Although it is still possible that other PMQR genes not yet identified are prevalent in E. coli , the above findings suggest that K. pneumoniae is more likely to develop fluoroquinolone resistance by obtaining PMQR genes than E. coli .…”
Section: Discussionmentioning
confidence: 94%
“…The widespread and predominance of CTX-M ␤ -lactamases have been confirmed in Europe, the Asia-Pacific region and South America [24,27,28] . CTX-M-type ESBLs were found to be responsible for most of the resistance to cephalosporin in Gram-negative isolates [29] . More investigations are needed to determine the specific types of CTX-M genes that are responsible for extended-spectrum cephalosporin resistance in our isolates.…”
Section: Citrobacter Freundiimentioning
confidence: 99%
“…Resistance to CIP in clinical isolates of E. coli obtained from blood cultures has reached 19% in Spain. In a recent study, 43% of E. coli isolates from the normal intestinal microflora of humans were found to be resistant to quinolones (2).…”
mentioning
confidence: 99%